Exploring the correlation of self-perception on the use of digital literacy in learning - Hasanah, Uswatun; Santoso, Anang; Pratiwi, Yuni; Sulthoni, Sulthoni; Farid, Mujahidin (Institute of Advanced Engineering and Science, 2024)
The rapid development of technology in the era of the fourth industrial revolution requires teachers to have good digital literacy competencies to present interactive, current, and adaptive learning. In line with this condition, this research aims to map prospective teachers’ digital literacy competency levels and explain the relationship between sub-areas of competency in digital literacy. The method used is quantitative, with validity testing using the reference value of item-total correlation, reliability testing using the reference value of Cronbach’s alpha, and normality testing using the Kolmogorov-Smirnov test. The levels of prospective teachers’ digital literacy competencies are mapped through descriptive quantitative analysis. Then, the correlation between competency areas is analyzed using bivariate correlation tests. The results of this study show that the majority of prospective teachers, accounting for 72.32%, have a moderate level of digital literacy competencies with a digital literacy index of 3.67. The relationship between measured sub-areas of digital literacy competencies shows a positive relationship. Still, it does not indicate a substantial correlation, indicating that more than the high scores on the digital literacy index and information is needed to support the competence of prospective teachers in creating digital content. This research is beneficial for higher education institutions in improving the digital literacy skills of prospective teachers. To enhance the digital literacy competencies of prospective teachers from a moderate level to a high level, there is a need for programs that strengthen the collaborative and communication sub-areas of competencies and programs that enhance the data and information literacy sub-areas.